How does COVID-19 Impact Oil Palm Management Practices in Indonesia? - Ratnawati Nurkhoiry; Sachnaz Desta Oktarina (International Journal of Oil Palm, 2020)
Disrupted economy due to COVID-19 pandemic has been spilled to multifaceted sectors. Agriculture, more specifically oil palm sector was also hit by the impact of the catastrophe. This study is aimed to decipher the effect of COVID-19 pandemic to the management of oil palm plantation. The pandemic has caused the mobility and morbidity of people in such a way that exacerbated distribution of input factor, harvesting process, and transporting activities. Through online survey to 59 farmers consist of smallholder, government, and private estates, the study indicated that there was salient change of limiting activities particularly during immature and mature stages. Hence, the production of fresh fruit bunch (FFB) also decreased by 15% compared to business as usual as measured on monthly bases. Although the magnitude of production change was not statistically significance, planters still suffered from declining FFB farm gate price. On average, they received 5% lower selling price of FFB as a consequence of contracted CPO demand from prominent importing countries such as China, India, and Italy. The lower selling farm gate price has caused the income shocks to the farmers. Thus, quite large number of them experienced either turn-over or cost efficiency at the expense of fertilizer input. It is perpetuating the vicious cycle of lower smallholder attainable FFB yield. For a group that is at the high risk of infections as well, this circumstances has bring about concerns to Indonesian palm oil development, especially in terms of replanting realization and biodiesel blending progress in the long run